Outdoor Therapy: An Interpretative Phenomenological Analysis Examining the Lived-Experience, Embodied, and Therapeutic Process through Interpersonal Process Recall - Heidi Schwenk (MDPI AG, 2019)
This research explores an innovative methodology for understanding the process and practice of UK-based outdoor therapists. Recent studies address the need to expand circles of knowledge, and capture the lived-experience of outdoor practitioners to examine the ‘altered’ therapeutic process and frame. Interpersonal process recall (IPR) methodology offers a nuanced and contextualised lived-experience of outdoor therapists. IPR includes three phases: (1) initial-interview; (2) post-session-reflective-recording; and (3) an IPR-interview to replay and explore the participants’ recorded reflections of the outdoor therapy session. The sample included three UK-based outdoor therapists. Interpretative phenomenological analysis was used to qualitatively analyze the data. The study presents the theme of ‘transitional landscapes—transitional thinking’, which explores the embodied experience, the parallel process between the client and therapist, and watching for drift. The findings provide insight for training and supervision and generates constructive dialogue amongst outdoor therapists. The research supports IPR as a methodology offering participant and researcher experiential and reflective positions. Parallels are drawn in relation to existing research, literature, and contemporary professional issues surrounding outdoor therapy as a mental health treatment.